2001
DOI: 10.1097/00004032-200101000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Depth Dose-Equivalent and Effective Energies of Photoneutrons Generated by 6–18 Mv X-Ray Beams for Radiotherapy

Abstract: Photoneutron production was investigated on Siemens KD 2 and Varian Clinac accelerators operating in the 6-18 MV range. Neutron dose equivalent rates were measured on the surface of a water phantom at the isocenter of the accelerators and also inside the phantom at depths of 1, 5, and 10 cm and off-axis distances of 0, 20, and 50 cm. Superheated drop detectors based on dichlorofluoromethane and etched-track detectors with boronated converters were employed in this study. The energy response of these detectors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 24 publications
3
45
0
Order By: Relevance
“…This difference in the energy of the initial electron, produce variations in the absorbed dose due to photons, and more specifically, its value at the isocenter, which, as already seen, can lead to differences in the values of H. Figure 13. Comparison of the dose equivalent normalized to the maximum due to neutrons calculated in this study, with published results by [8] and [19].…”
Section: Dose Equivalent Due To Neutronsmentioning
confidence: 56%
See 3 more Smart Citations
“…This difference in the energy of the initial electron, produce variations in the absorbed dose due to photons, and more specifically, its value at the isocenter, which, as already seen, can lead to differences in the values of H. Figure 13. Comparison of the dose equivalent normalized to the maximum due to neutrons calculated in this study, with published results by [8] and [19].…”
Section: Dose Equivalent Due To Neutronsmentioning
confidence: 56%
“…It is concluded that phantom behaves as a moderador of neutrons due to its high content of 1 H, just 11.1% of total the ICRU phantom, with a threshold of thermal production of only 2.2 MeV [8]. …”
Section: Icru Phantom In Front Of a Neutron Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6] In addition, secondary radiation may lead to radioactivation in the treatment room. Therefore, the evaluation of neutron dose is important in the medical field.…”
mentioning
confidence: 99%